2013
DOI: 10.5152/ucd.2013.37
|View full text |Cite
|
Sign up to set email alerts
|

Quality of life after stapler haemorrhoidectomy evaluated by SF-36 questionnaire

Abstract: Objective: Hemorrhoids are normal elements of the anal canal anatomy and they become symptomatic with potential factors such as gravity or strain. When symptomatic, hemorrhoidal disease can be costly measured in time away from productive activities. The aim of the study was to assess changes in the quality of life of patients after hemorrhoidectomy using Short Form-36. Material and Methods:Thirty patients, 24 male and 6 female (age 28 to 65), who were diagnosed with grade III and IV internal hemorrhoidal disea… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

1
3
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 13 publications
1
3
0
Order By: Relevance
“…Notably, Rørvik's cross-sectional and cohort analysis using multiple QoL scales, including SF-12, SF-36, EuroQoL 5-dimensions 5-levels, and Short Health Scale for hemorrhoidal disease, revealed significant QoL enhancements, similar to the findings from Martinsons's randomized trial comparing conventional hemorrhoidectomy and stapled hemorrhoidopexy (31,32). Erdogdu's research further corroborates these results, with significant post-surgical improvements in physical health scores assessed by SF-36 (33). Garg's observational study using the WHOQOL-BREF highlighted improvements in physical and psychological well-being one month post-stapled hemorrhoidopexy, though social domains showed minimal change (16).…”
Section: Discussionsupporting
confidence: 60%
“…Notably, Rørvik's cross-sectional and cohort analysis using multiple QoL scales, including SF-12, SF-36, EuroQoL 5-dimensions 5-levels, and Short Health Scale for hemorrhoidal disease, revealed significant QoL enhancements, similar to the findings from Martinsons's randomized trial comparing conventional hemorrhoidectomy and stapled hemorrhoidopexy (31,32). Erdogdu's research further corroborates these results, with significant post-surgical improvements in physical health scores assessed by SF-36 (33). Garg's observational study using the WHOQOL-BREF highlighted improvements in physical and psychological well-being one month post-stapled hemorrhoidopexy, though social domains showed minimal change (16).…”
Section: Discussionsupporting
confidence: 60%
“…As in our study, several studies have used the SF-36 questionnaire to assess improvement in this outcome after available treatments. 34,35 However, as far as we know, this is the first time that quality of life has been analyzed in pregnant women. Because the SF-36 assesses the non-disease-specific perception of quality of life, in our study we also used an ad hoc method to evaluate the specific impact of hemorrhoidal disease on quality of life by using a scale from 0 to 10.…”
Section: Discussionmentioning
confidence: 99%
“…They demonstrated that physical health (physical functioning, physical role restriction, and bodily pain) scores significantly improved after surgery. 16 Bouchard et al in a multicenter trial followed patients who underwent hemorrhoidectomy for 1 year and reported that all physical and mental domains of quality of life significantly improved, and 88% of patients were satisfied or very satisfied by the surgery. [15][16][17][18] The common postoperative complications in laser surgeries include delayed bleeding, presence of urinary retention, painful defecation, fistula, acute infection fissure, anal stenosis, fecal incontinence, and postoperative thrombosis.…”
Section: Discussionmentioning
confidence: 99%
“…16 Bouchard et al in a multicenter trial followed patients who underwent hemorrhoidectomy for 1 year and reported that all physical and mental domains of quality of life significantly improved, and 88% of patients were satisfied or very satisfied by the surgery. [15][16][17][18] The common postoperative complications in laser surgeries include delayed bleeding, presence of urinary retention, painful defecation, fistula, acute infection fissure, anal stenosis, fecal incontinence, and postoperative thrombosis. None of mentioned complications were observed in any of our patients within 6 months after surgery.…”
Section: Discussionmentioning
confidence: 99%